Anthropometric and body composition changes in smokers vs abstainers following an exercise-aided pharmacotherapy smoking cessation trial for women. (October 2018) - Prapavessis, Harry; De Jesus, Stefanie; Fitzgeorge, Lyndsay; Rollo, Scott
Abstract: Introduction: Post-cessation weight gain contributes to smoking relapse, especially for women. Furthermore, excess weight in the form of android or visceral fat is associated with metabolic health problems. For this study, a secondary analysis was conducted in 2015 to determine whether quitting status, achieved through a 14 week supervised exercise-aided nicotine replacement therapy (NRT) cessation program [Getting Physical on Cigarette Trial-2009 to 2013; Prapavessis, et al., 2016], affects anthropometric and body composition parameters in female smokers ( N  = 413, M age = 42.39 years). Methods: Anthropometric (weight and BMI) and body composition (% total body fat, % android fat, lean mass and visceral fat) indices were assessed at baseline and end of treatment. Smoking status was confirmed weekly from expired breath carbon monoxide. Adherence to exercise and NRT patch was calculated from the number of exercise sessions attended and patches worn to the number of exercise sessions offered and patches supplied, respectively. Results: Factorial (smoking status) ANCOVAs controlling for baseline anthropometric and body composition parameters as well as adherence to exercise and NRT revealed significant differences in weight ( p  = .033; ɳp 2  = 0.017) and BMI ( p  = .020; ɳp 2  = 0.020) at week 14. This equated to abstainers weighing 1.26 kg more and having a 0.52 higher BMI than smokers. No significant differences were found for any of the body composition parameters at week 14 (ɳp 2 range from 0.001–0.007). Conclusions: Abstainers gain modest weight compared to smokers. This weight gain is related to increases in lean mass and not total, android, or visceral fat. Highlights: Weight gain associated with quitting was minimal for women completing the "Getting Physical on Cigarettes" trial. The minimal weight gain for abstainers was related to an increase in lean mass and not to an increase in fat. Exercise-aided smoking cessation programs are recommended to manage weight and body composition indices.